Perubahan Warna, Tekstur, Densitas dan Komposisi sebagai Parameter Tingkat Ketuaan Buah Mangga Arumanis - Atris Suyantohadi; Guntarti Tatik Mulyati (agriTECH, 2001)
This research was aimed to analysis the change of fruit by physical factors i.e. color change around the fruit branch, fruit texture, fruit density, and by chemical factors i.e, content of total sugar, total acids, starch and pH value. They were continuosly monitored based on the fruits ages criterion from unripe (green fruits) to ripe fruits. The Determination was counted from unripe fruits to ripe fruits stage (from 65 days to 122 days after flowering). Fruits taken from mango plantation in Watugadjah, Gunung Kidul, Yogyakarta, were selected from some of mango trees which had simultaneous flowered. The result showed that the level of fruit color and fruit density increased but fruit texture decreased. Acids contents decreased but total sugar and total starch increased up to fruits ripening at the trees. The characteristics of ripening "arumanis" mango ranged 45-90 for lightness; 88-90 for texture; 5.6-6.5%, 4.0-5.5% for starch and sugar content respectively, and 3.0-3.5 for pH.